Uncertain multilevel programming: Algorithm and applications. (November 2015) - Liu, Baoding; Yao, Kai
Highlights: Proposing an uncertain multilevel programming model. Deriving the equivalent crisp model. Application in a production control problem. Abstract: Multilevel programming is used to model a decentralized planning problem with multiple decision makers in a hierarchical system. This paper aims at providing an uncertain multilevel programming model that is a type of multilevel programming involving uncertain variables. Besides, a genetic algorithm is employed to solve the model. As an illustration, the uncertain multilevel programming model is applied to a product control problem.